National Consensus Statement on the Management of Type 2 Diabetes Mellitus in Nepal - Shrestha, Dina; Shrestha, Pradeep; Sharma, Sanjib; Bhattarai, Jyoti; Shrestha, Hari Kumar; Pradhan, Ajay; Shakya, Amit (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
The full National Consensus Statement on the Management of Type 2 Diabetes Mellitus in Nepal is included here.